Cigarette smoke exposure during adolescence enhances sensitivity to the rewarding effects of nicotine in adulthood, even after a long period of abstinence. (December 2015) - de la Peña, June Bryan; Ahsan, Hafiz Muhammad; Tampus, Reinholdgher; Botanas, Chrislean Jun; dela Peña, Irene Joy; Kim, Hee Jin; Sohn, Aeree; dela Peña, Ike; Shin, Chan Young; Ryu, Jong Hoon; Cheong, Jae Hoon
Abstract: Adolescence is a period of enhanced vulnerability to the motivational properties of tobacco/cigarette smoking. Several studies have suggested that smoking initiation during this period will more likely lead to long-lasting cigarette or nicotine addiction. In the present study, we investigated the influences of adolescent cigarette smoke or nicotine exposure on the rewarding effects of nicotine, particularly whether these influences persist even after a long period of abstinence. Towards this, adolescent and adult Sprague–Dawley rats were repeatedly exposed to cigarette smoke or nicotine, for 14 days, and then were subjected to a 1-month abstinence period. Thereafter, the rewarding effects of nicotine were evaluated through the conditioned place preference (CPP) and self-administration (SA) tests. Even after a 1-month abstinence period, rats pre-exposed to either nicotine or cigarette smoke demonstrated enhanced CPP for the higher dose (0.6 mg/kg) of nicotine. Notably, cigarette smoke-preexposed adolescent rats, now adults, showed CPP for both 0.2 and 0.6 mg/kg dose of nicotine. Moreover, only these rats (pre-exposed to cigarette smoke during adolescence) showed significant acquisition and maintenance of nicotine (0.03 mg/kg/infusion) SA. These results suggest that cigarette smoke exposure during adolescence enhances sensitivity to the rewarding effects of nicotine in adulthood, even after a long period of abstinence. This may be a factor in the high rates of nicotine addiction and dependence observed in smokers who started during adolescence. More importantly, our findings highlight the enduring consequences of adolescent-onset cigarette smoking and the need to protect this vulnerable population. Highlights: Tobacco/cigarette smoking typically starts during adolescence. Adolescents are highly sensitive to the motivational/addictive effects of nicotine. Adult rats exposed to cigarette smoke in adolescence showed enhanced nicotine CPP. Adult rats exposed to cigarette smoke in adolescence demonstrated nicotine SA. The effects of adolescent-onset cigarette smoke exposure are long lasting.